2016
DOI: 10.1007/s12032-016-0757-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of circulating miRNA detection in lung cancer

Abstract: Lung cancer is the most common cancer in the world and the leading cause of tumor death among males. MicroRNAs (miRNAs) are single-stranded RNAs of approximately 22 nucleotides and constituted a new class of gene regulators in humans. As a novel class of emerging biomarkers, the aberrant expression of miRNA has been detected in various tumors. miRNAs are secreted into circulation by microvesicles from the broken tumor cells and act as either oncogenes or tumor suppressors in tumor tissues. In this review, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Regulatory ncRNAs can be further divided into two groups based on their size: small ncRNAs (shorter than 200 nucleotides) and lncRNAs (200 nucleotides or longer). Small ncRNAs contain microRNAs, small nucleolar RNAs (snoRNAs), small interfering RNAs (siRNAs), small nuclear RNAs (snRNAs), and PIWI-interacting RNAs (piRNAs) (Figure 1) [49,50,51]. …”
Section: Non-coding Rnamentioning
confidence: 99%
See 3 more Smart Citations
“…Regulatory ncRNAs can be further divided into two groups based on their size: small ncRNAs (shorter than 200 nucleotides) and lncRNAs (200 nucleotides or longer). Small ncRNAs contain microRNAs, small nucleolar RNAs (snoRNAs), small interfering RNAs (siRNAs), small nuclear RNAs (snRNAs), and PIWI-interacting RNAs (piRNAs) (Figure 1) [49,50,51]. …”
Section: Non-coding Rnamentioning
confidence: 99%
“…MicroRNAs comprise one of the most abundant classes of gene regulatory molecules and therefore influence the output of many protein-coding genes [52]. MicroRNAs have the potential to serve as biomarkers and therapeutic tools for different cancer subtypes, as classified by origin, histology, aggressiveness, or chemosensitivity [37,38,39,40,45,46,47,48,49]. Importantly, in comparison to mRNAs, microRNAs are markedly less degraded in formalin-fixed paraffin-embedded (FFPE) samples, which are typically collected and stored in hospitals.…”
Section: Non-coding Rnamentioning
confidence: 99%
See 2 more Smart Citations
“…12 For this reason, CTCs can be used to predict the potential of distant metastases and prognosis of cancer patients. 13 Recently, a prospective multicenter study by Cohen et al 14 confirmed that the number of CTCs before and during treatment could be an independent predictor of progression-free survival (PFS) and overall survival (OS) in patients with mCRC. CTCs provided prognostic information in addition to that of imaging studies.…”
Section: Introductionmentioning
confidence: 99%